2009
DOI: 10.1538/expanim.58.333
|View full text |Cite
|
Sign up to set email alerts
|

National BioResource Project-Rat and Related Activities

Abstract: Abstract:In order to establish a system to facilitate the systematic collection, preservation, and provision of laboratory rats (Rattus norvegicus) and their derivates, the National BioResource Project-Rat (NBRP-Rat) was launched in July 2002. By the end of 2008, more than 500 rat strains had been collected and preserved as live animals, embryos, or sperm. These rat resources are supplied to biomedical scientists in Japan as well as in other countries. This review article introduces NBRP-Rat and highlights the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 27 publications
0
62
0
Order By: Relevance
“…The laboratory rat (Rattus norvegicus) has been widely used as an animal model of human diseases, because its size is suitable for manipulation [1,27]. Sequencing of the rat genome has shown that the rat has about 20,000 predicted genes and shares as many as 90% with humans [9].…”
Section: Introductionmentioning
confidence: 99%
“…The laboratory rat (Rattus norvegicus) has been widely used as an animal model of human diseases, because its size is suitable for manipulation [1,27]. Sequencing of the rat genome has shown that the rat has about 20,000 predicted genes and shares as many as 90% with humans [9].…”
Section: Introductionmentioning
confidence: 99%
“…The laboratory rat (Rattus norvegicus) has been widely used as an animal model of human diseases, because its size is suitable for manipulation [1,12]. The rat model system is also used for understanding gene function.…”
mentioning
confidence: 99%
“…KFRS5A/Kyo strains were obtained from the National BioResource Project -Rat (NBRP-Rat) [12]. For histopathology, dorsal skins were collected from Re/Re, Re/+, and wild-type (+/+) rats, fixed in 10% buffered formalin, and embedded in paraffin.…”
mentioning
confidence: 99%
“…The tracer was delivered into proximal dorsal tail vein using a Model NE-1000 syringe pump (New Era Syringe Pumps, Farmingdale, NY) via 0. ( 16 ). The tracer infusion had no effect on the level of plasma FFA.…”
Section: Isotope Infusion and Tissue Collectionmentioning
confidence: 87%